Does Place of Birth Affect the Anthropometric and Performance Characteristics of Papua New Guinean Athletes? - Kieran Sciberras; Glen B. Deakin; Aaron Alsop; Stephen P. Bird (International Universities Strength and Conditioning Association, 2024)
Previous research has indicated that region of origin may influence the anthropometric and performance characteristics of an individual. The aim of this study was to determine the anthropometric and performance characteristics of Papua New Guineans and examine the relationship with the region of origin. 1176 Papua New Guinean athletes (666 males/510 females) aged between 14 and 39 years old completed anthropometric testing (height, seated height, arm span, body mass, body mass index), performance testing (sit and reach, medicine ball throw, vertical jump, Illinois agility, 5m/20m sprint, 60 second push-up/sit-up, multi-stage fitness test) and a heritage questionnaire (participant's place of birth). Participants that met required criteria were categorised by ages groups (15-17 years, 18-20 years, 21-25 years and 26-30 years), sex (male and female) and by birth province (National Capital District, Morobe, Central, Sandaun, East Sepik, East New Britain, West New Britain and Milne Bay) before statistical analysis. Significant differences between birth provinces of participants were found for all tested anthropometric and performance characteristics (p<0.05), except for the leg length and Illinois agility test. Significant differences (p<0.05) were also found for all but one (body mass index) tested characteristics between the two sexes. Analysis of age indicated a significant difference for tested characteristics between age groups (p<0.05). Further analyses revealed that while birth province had an effect on some characteristics, sex and age demonstrated a significant and larger influence. Consequently, whilst there may be an association between the region of origin and anthropometric and performance characteristics of Papua New Guinean athletes, other variables such as sex and age also significantly influence anthropometric and performance characteristics.